Quality indicators for colonoscopy in Peruvian national hospitals: a multicenter cross-sectional study - Leon-Quispe, Diego A. (2026)
Objectives: To evaluate colonoscopy quality indicators in Peruvian national public hospitals and to estimate the polyp detection rate (PDR) corresponding to adenoma detection rate (ADR) benchmarks of 25% and 35%. Materials and methods: A multicenter retrospective study was conducted using colonoscopy reports from July 2023 to June 2024. Rates of adequate bowel preparation and cecal intubation, as well as withdrawal time, polypectomy technique, PDR, and ADR were evaluated. Results: A total of 3,758 colonoscopies performed by 63 endoscopists were analyzed. The rate of adequate bowel preparation was 91.1%, and the cecal intubation rate was 95.6%. The withdrawal time was not reported in 75% of procedures without polyp detection. Only 30.2% of polyps measuring 4–9 mm were removed using cold snare polypectomy. The overall PDR was 41.3%, and the overall ADR was 22.8%. The adenoma-to-polyp detection rate quotient was 0.56; a PDR of 62.5% corresponded to an ADR of 35%, and a PDR of 44.7% to an ADR of 25%. Conclusions: Colonoscopy quality in Peruvian national public hospitals showed adequate rates of bowel preparation and cecal intubation but suboptimal ADR values and deficient documentation practices, underscoring the need to implement targeted strategies to improve colonoscopy quality.